Management of Snake Bites in the Agricultural Sector - Kholid Rosyidi Muhammad Nur; Enggal Hadi Kurniyawan; Mayang Dwi Puja Lestari; Aryani Ayuning Tyas; Septia Salzabilla Flaurenza; Ritha Ayu Setyaningrum; Kumala Dewi (KHD Production, 2023)
Snake bites are the one that causes high rates of morbidity and mortality among workers in the agricultural sector. Snake bites can be a medical emergency that can endanger human life, and snake venom can damage local tissues, resulting in permanent disability and amputation. This study aims to identify farmers' knowledge related to snakebite management. A literature review searched three databases, Google Scholar, ScienceDirect, and PubMed, for all study designs between 2019 and 2023. The researcher found ten studies that met the inclusion criteria in the review. The high risk of snake bites for farmers makes it essential for farmers to know the most critical things in snakebite management. When bitten by a snake, the most important thing to do is first aid treatment in a threatening situation. Some factors that can affect the management of snake bites on farmers are the characteristics of farmers who are usually male with a low educational background and level of knowledge. In addition, low experience will affect the ability to handle first aid. Nurses can be present as extension workers to increase farmers' knowledge about first aid for snake bites to farmers.